2022
DOI: 10.3390/jcm11206060
|View full text |Cite
|
Sign up to set email alerts
|

Is SARS-CoV-2 a Risk Factor of Bipolar Disorder?—A Narrative Review

Abstract: For 2.5 years we have been facing the coronavirus disease (COVID-19) and its health, social and economic effects. One of its known consequences is the development of neuropsychiatric diseases such as anxiety and depression. However, reports of manic episodes related to COVID-19 have emerged. Mania is an integral part of the debilitating illness—bipolar disorder (BD). Due to its devastating effects, it is therefore important to establish whether SARS-CoV-2 infection is a causative agent of this severe mental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 298 publications
(496 reference statements)
0
11
0
Order By: Relevance
“…Although mania has sometimes been reported in the context of COVID-19 infection, the pathophysiology is far from elucidated. Hypotheses are being developed that take into account factors such as inflammation, changes in genetics and epigenetics, metabolism, hormones, neurotransmission, immunology, and oxidative stress [ 15 ]. Even though the virus has been shown to invade the central nervous system, a clear clinical correlation between positive CSF PCR testing and neuropsychiatric symptoms has not been identified [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although mania has sometimes been reported in the context of COVID-19 infection, the pathophysiology is far from elucidated. Hypotheses are being developed that take into account factors such as inflammation, changes in genetics and epigenetics, metabolism, hormones, neurotransmission, immunology, and oxidative stress [ 15 ]. Even though the virus has been shown to invade the central nervous system, a clear clinical correlation between positive CSF PCR testing and neuropsychiatric symptoms has not been identified [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, immune system disturbances are also considered to be the major determinant of neuroinflammatory processes that feature in both the etiology and the course of bipolar disorder ( Kirlioglu et al, 2019 ). COVID-19 has been found to be related to cytokine dysregulations, tryptophan metabolism alterations, sleep disorders, and structural changes in the CNS that are similar to BD ( Lorkiewicz and Waszkiewicz, 2022 ). It is suggested that all these changes may trigger or unmask the development of BD ( Lorkiewicz and Waszkiewicz, 2022 , Del Casale et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 has been found to be related to cytokine dysregulations, tryptophan metabolism alterations, sleep disorders, and structural changes in the CNS that are similar to BD ( Lorkiewicz and Waszkiewicz, 2022 ). It is suggested that all these changes may trigger or unmask the development of BD ( Lorkiewicz and Waszkiewicz, 2022 , Del Casale et al, 2022 ). In addition, our patient had a severe illness which may be related to the emergence of neuropsychiatric manifestations, which are considered to worsen the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is speculative comparison of COVID-19 symptoms to bipolar disorders, citing the commonality of cytokine disorder, sleep disorders, and tryptophan metabolism in both (Lorkiewicz & Waszkiewicz, 2022). ADHD poses increased risk for COVID-19 but may reduce risk of severe outcomes.…”
Section: Covid-19 Neuroinflammationmentioning
confidence: 99%